Analysis of Collaborative Development of E-commerce in Agricultural Product Logistics - Zeng, Yiyong; Wang, Zhisheng; Zhang, Dejiang (Journal of Theory and Practice of Management Science, 2024)
Guangdong province as one of the most developed area in economy in our country, the agricultural products as an important form of economy, in the process of e-commerce development in recent years, agricultural products sales gradually shift to online mode, but limited to the conditions of logistics, make a lot of damage in the process of logistics of agricultural products, affect agricultural electricity benefit and reputation. Therefore, this paper aims to study the cooperative development mode of guangdong agricultural products logistics and e- commerce, so as to promote the development of guangdong agricultural products industry. In the prevention and control of the novel coronavirus pneumonia epidemic, information and technology empowered the digital governance of serious epidemics. The crisis is a turning point, and digital governance has further advanced the development process of the modernization of the national governance system and governance capabilities. This article introduces the practical experience of digital governance in the prevention and control of the novel coronavirus pneumonia epidemic, expounds the active role of digital governance in epidemic monitoring, joint prevention and control, resumption of work and production, and social governance, and analyzed some of the problems exposed when digital governance was applied to serious epidemic prevention and control with great success. Finally looked forward to the future development of digital governance.